2022
DOI: 10.1371/journal.pone.0274202
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial working conditions and chronic low-grade inflammation in geriatric care professionals: A cross-sectional study

Abstract: Background Chronic low-grade inflammation has been suggested as a key factor in the association between stress exposure and long-term health. Care work is recognized as a profession with a high degree of job stress and health risks. However, for care professionals, the study base on inflammatory activity due to adverse working conditions is limited. Objective The aim of this study was to explore associations between self-reported psychosocial working conditions and care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 85 publications
0
2
0
1
Order By: Relevance
“…In hospital employees, respective investigations are sparse. One recent study surprisingly found a positive relationship of job autonomy and CRP among geriatric care professionals, perhaps due to greater responsibilities and experiences of excessive demands (Kaltenegger et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In hospital employees, respective investigations are sparse. One recent study surprisingly found a positive relationship of job autonomy and CRP among geriatric care professionals, perhaps due to greater responsibilities and experiences of excessive demands (Kaltenegger et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Especially in healthcare, there have been fundamental advancements in terms of health information technology (e.g., electronic health records, computerized decision support systems; Abbott and Weinger 2020 ). At the same time, healthcare professionals are already exposed to a high degree of work stress putting them at an increased risk for adverse health outcomes (Dawe et al 2016 ; Adriaenssens et al 2015 ; Kaltenegger et al 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…К основным технострессорам относятся техно-и информационная перегрузка [38,[40][41][42], техническая сложность процесса, нарушения в работе информационно-коммуникационных технологий [41], многозадачность, неудобство использования техники в целом и отсутствие своевременной технической поддержки [43]. Медицинские работники подвергаются высокому стрессу на работе, что способствует повышенному риску развития неблагоприятных последствий для здоровья [44][45][46].…”
Section: социальные стрессоры и воспалениеunclassified